False-positive FDG PET CT Scan in Vertebral Hemangioma - Shrikant Solav; Shailendra Salve; Abhijit Patil (Asia Oceania Journal of Nuclear Medicine and Biology, 2019)
FDG PET CT scan is considered to be a sensitive tool to detect skeletal metastasis in known malignancies. However, it’s high sensitivity and low specificity may account for false positive diagnosis in cases of trauma, infection, inflammation and other benign conditions. Skeletal hemangioma is one of the common benign conditions which are typically ametabolic on FDG PET CT with no uptake on bone scan. However, rarely they may have atypical imaging features and appear hypermetabolic. Other imaging modalities such as MRI and CT scan have typical imaging findings for hemangioma and can be used for evaluation of focal hypermetabolic skeletal lesions. There are atypical imaging characteristics in each of these modalities. Hence when used judiciously they can complement each other and avoid a false positive test result. This case report highlights the importance of bone scan and CT scan in excluding pathological involvement of skeleton with false positive FDG PET scan results.